The Mediatized Conditions of Contemporary Religion Critical Status and Future Directions. - Lovheim, M.
During the last decade the framework of mediatization theory has been introduced in the field of media, religion and culture as a parallel perspective to the ?mediation of religion? approach, allowing new questions to be posed that align with religious change within Europe. This article provides a critical review of existing research applying mediatization of religion theory, focusing on key issues raised by its critics as well as how the theory have moved the research field forward. These issues concern the concept of religion, institution and social change, religious authority, and the application of mediatization theory outside the North-Western European context where it originated. The article argues that an institutional approach to mediatization is a relevant tool for analyzing change as a dynamic process in which the logics of particular forms of media influence practices, values and relations within particular manifestations of religion across various levels of analysis.